Formation of high-density polyethylene–poly(ethylene-octene) core–shell particles in recycled poly(ethylene terephthalate) by reactive blending. Issue 3 (August 2019) - Liu, Yongjun; Zhong, Ming; Liu, Gang; Pu, Shouzhi
Recycled poly(ethylene terephthalate) (R-PET)/high-density polyethylene (HDPE)/glycidyl methacrylate grafted poly(ethylene-octene) (mPOE) blends, in which the binary (HDPE/mPOE) dispersed phase was of a HDPE core-mPOE shell structure, were prepared. For this purpose, HDPE-g-mPOE graft copolymers were prepared in HDPE/mPOE blends via reactive extrusion with the presence of the free radical initiator dicumyl peroxide (DCP). Then, R-PET was blended with the HDPE/mPOE blends by melt extrusion. The effect of the DCP and mPOE content in the HDPE/mPOE blends on the phase morphology and mechanical properties of the R-PET/HDPE/mPOE blends were studied systematically. It was found that the blends containing reactive compatibilizer exhibited the encapsulation of the HDPE by the mPOE, forming core–shell particles dispersed phase morphology. The graft chains of HDPE-g-mPOE-g-PET formed by the in situ reaction between R-PET and mPOE phases reduced the interfacial tension. Consequently, the dispersed phase morphology was observed to form smaller diameter core–shell particles. The resultant blends exhibited an effect on both the thermal and mechanical properties. Differential scanning calorimetric analysis showed the dispersed phase particles could act as a nucleating agent in the R-PET matrix to improve the crystallization temperature, while the graft copolymers formed in the compatibilized R-PET/HDPE/mPOE blend decreased the nucleation activity. Notched Charpy impact strength and elongation at break of the R-PET were improved by forming the core–shell particles dispersed phase morphology.